Longitudinal Whole-Brain N-Acetylaspartate Concentration in Healthy Adults - Rigotti, D.J.; Kirov, I.I.; Djavadi, B.; Perry, N.; Babb, J.S.; Gonen, O. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Although NAA is often used as a marker of neural integrity and health in different neurologic disorders, the temporal behavior of WBNAA is not well characterized. Our goal therefore was to establish its normal variations in a cohort of healthy adults over typical clinical trial periods. MATERIALS AND METHODS: Baseline amount of brain NAA, QNAA, was obtained with nonlocalizing proton MR spectroscopy from 9 subjects (7 women, 2 men; 31.2 ± 5.6 years old). QNAA was converted into absolute millimole amount by using phantom-replacement. The WBNAA concentration was derived by dividing QNAA with the brain parenchyma volume, VB, segmented from MR imaging. Temporal variations were determined with 4 annual scans of each participant. RESULTS: The distribution of WBNAA levels was not different among time points with respect to the mean, 12.1 ± 1.5 mmol/L (P > .6), nor was its intrasubject change (coefficient of variation = 8.6%) significant between any 2 scans (P > .5). There was a small (0.2 mL) but significant (P = .05) annual VB decline. CONCLUSIONS: WBNAA is stable over a 3-year period in healthy adults. It qualifies therefore as a biomarker for global neuronal loss and dysfunction in diffuse neurologic disorders that may be well worth considering as a secondary outcome measure candidate for clinical trials. CVcoefficient of variationGMgray matter1H-MRSproton MR spectroscopyMPRAGEmagnetization-prepared rapid acquisition of gradient echoNAAN-acetylaspartateQNAAabsolute amount of NAA (millimoles)SNRsignal intensity–to-noise ratioSRreference NAA peak areaSSsubject NAA peak areaVOIvolume of interestVR180°reference transmitter voltageVS180°= subject transmitter voltage; WBNAAwhole-brain NAA concentrationWMwhite matter